Revitalisasi Pemupukan Padi Sawah Berbasis Lingkungan - Erythrina, Erythrina; Zaini, Zulkifli (Iptek Tanaman Pangan, 2015)
IAARD in the Ministry of Agriculture has produced a wide range of technology for site specific nutrient management (SSNM), in form of soil-test kit equipment and software. This paper presents the concept of revitalization the system and direction for an efficient fertilization usage. A more rational use of fertilizers based on a specific locational need is expected in the long term to reduce the amount of fertilizer subsidies, without reducing the rice production. The effect of SSNM had been shown to give opportunities for yield increases per unit of fertilizer, to reduce loss of fertilizer, to improve agronomic efficiency and at the same time had positive influence on the environment. SSNM could be used to develop plan for fertilizer requirement per farmersâ€™ group (RDKK) which in reality was often not compiled by field extension in accordance with the area of land and fertilizer needs. Inaccurate RDKK preparation had been causing problem on the distribution of subsidized fertilizer, because it was often showing an overestimate of the amount of fertilizer needed, as compared with the availability of fertilizer. Funds allocated for the preparation of RDKK could be routed to the procurement of hardware such as computers and to train the agricultural extension workers in each Agricultural Extension Center in Indonesia, to be able to access the website-specific nutrient fertilization through the internet. Assessment Institute of Agricultural Technology located in every province could facilitate this technology transfer process.Â